MODELO DIDÁTICO DE ROLEPLAYING GAME (RPG) LOST MINE OF PHANDELVER PARA O ENSINO DE INGLÊS COMO LÍNGUA ESTRANGEIRA - Ramos, Élen (2017)
The aim of this study is to build up a didactic model that provides an understanding of the RPG teachable dimensions for teaching English as a foreign language, because we believe that a deep understanding of the dimensions that constitute it is required by the teacher. Therefore, we used the sociodiscursive interacionism theoretical assumptions (BRONCKART, 1999; 2006a; 2006b; 2008), in the analysis of the architecture of the texts, the didactic of languages (SCHNEUWLY; DOLZ, 2004), that uses genres as teaching megatools, and the grammar of visual design (KRESS; VAN LEEUWEN, 2006), which helps us to understand, read and create the meanings of images. Our corpus of analysis is a RPG campaign book called Lost Mine of Phandelver (WIZARDS OF THE COAST, 2014d) that belongs to the Dungeons & Dragons system of rules. We used the qualitative and quantitative approach, the documental and bibliographic research procedures and we analyzed the corpus by the criteria of the two previously mentioned theoretical perspectives. The subject content of this campaign refers to the medieval era and Tolkien’s Middle-earth. The types of discourses found were: the narration, which presents the story to be told; the interactive discourses, which refers to the instructions to be followed by the master; and, the interactive report, which is related to the instructions directed to the characters. We noticed implicit and explicit voices of characters and evaluations of the text by the modalizations: logical, which shows the possibilities within the story; deontic, which points out what is allowed or not to be done in the game according to the rules; appreciative, which classify the dimensions as good and bad before the morality of a society; and, pragmatic, which exposes what the player can, wants or must do according to his will. The classifications that take us to the understanding of the images can be taught to the students by the metalanguage, or by inducing them, through questions, to interpret the images. Games are present in the foreign language classes to motivate the students, help them in their assimilation of the contents and to the interaction between the students and the teacher. RPG has these properties and it even instigates the oral production and the socialization, because it is a game of collaborative creation of storytelling. We hope this study can be a support for theoretically grounded works and it guides classes with the game for introduction, complement, for fixation or ending of contents.